Plasma cell leukaemia - Braga, Carlos Galvão (Porto Biomed J, 2016)
Plasma cell leukaemia (PCL) is a rare and aggressive disease. Diagnosis is made when there are >2000/#mL circulating plasma cells in peripheral blood or plasmacytosis >20% of total leukocyte count. We report a case of a 51-year old man with generalized bone pain and constitutional symptoms. Blood peripheral smear revealed leukocytosis with 39% plasma cells. Bone marrow biopsy showed plasma cell invasion, which confirmed the diagnosis of PCL. Additionally, the patient had markers of advanced disease. Chemotherapy with vincristine, adriamycin and dexamethasone was started. Despite an initial favourable response, the patient died 2 months later due to an infectious complication. PCL has no established treatment and has a dismal prognosis, requiring the achievement of better data to improve the disease course.